RESOLUSI KONFLIK LAHAN HAK GUNA USAHA PT. ALAM SARI LESTARI DI KABUPATEN INDRAGIRI HULU - Ika May Indrawati; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Land is one of the most basic state assets. Land for human life has a very important role, because all activities are carried out on the ground. Therefore, land is very much needed by every community, so it is not surprising that there are so many conflicts. One of which is the conflict between PT. Alam Sari Lestari with Sekip Hilir Village in Indragiri Hulu Regency. Starting from the uncertainty of the location of the PT. Alam Sari Lestari which is written in the Minutes of the Land Inspection Committee B Riau Province with what is written in the Measurement Letter and also the Certificate. This study aims to determine the inhibiting factors for conflict resolution and how the role of the government in conducting conflict resolution at PT. Alam Sari Lestari in Indragiri Hulu Regency. Then using the data analysis technique model of Miles and Huberman in Yusuf (2017). This research is a descriptive qualitative research where the data collection uses observation, interview, and documentation techniques. This study uses the theory of resolution proposed by Fisher in (Tisa, 2017), namely Negotiation, Mediation, and Arbritation. The research result show that of the entire existing resolutions, the government as a third party that has no interest in the stage of finding the results, because one of the parties in the conflict did not follow the process. So that the next stage has not been carried out and the efforts made by the local government of Indragiri Hulu Regency have not been able to run optimally.Keyword: Resolution, Conflict, Land Conflict